2014
DOI: 10.1016/j.funeco.2014.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Mycothalli of the hepatic Barbilophozia hatcheri in Antarctica: distribution and identities of mycobionts

Abstract: Forty-four herbarium specimens of the hepatic Barbilophozia hatcheri, collected from across the entire range of the species in Antarctica (54-68 °S), were examined for fungal colonisation. Mycothalli, consisting of hyaline hyphae in rhizoids or hyphal coils in rhizoid bases and stem medullary cells, were present in 42 specimens. The frequencies of mycothalli declined at higher latitudes and were associated positively with annual air 20 temperatures. In contrast, the frequency of dark septate hyphae on stems in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
(10 reference statements)
1
3
0
Order By: Relevance
“…Previous studies using electron microscopy have shown the presence of heterobasidiomycetes with dolipore septa and imperforate parenthosomes-which were most probably members of Serendipita-forming tightly convoluted, intracellular hyphal coils in the tissues of liverworts in these families and in those of the Arnelliaceae, Jungermanniaceae, Geocalycaceae and Scapaniaceae (Read et al 2000;). The study here, based on epifluorescence microscopy and PCR amplification of fungal ribosomal RNA genes, closely corroborates these observations, with the frequency of Serendipita being positively associated with the abundance of intracellular hyphal coils, identical to those previously recorded in European and Antarctic Diplophyllum albicans, Schistochilopsis incisa, Barbilophozia hatcheri, Trilophozia quinquedentata and Lophoziopsis excisa Newsham & Bridge 2010;Newsham et al 2014). The analyses here also indicate that Serendipita most probably does not form DS hyphae, with melanized hyphae being absent from, or present at very low levels in, specimens from which the DNA of the basidiomycete was amplified.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Previous studies using electron microscopy have shown the presence of heterobasidiomycetes with dolipore septa and imperforate parenthosomes-which were most probably members of Serendipita-forming tightly convoluted, intracellular hyphal coils in the tissues of liverworts in these families and in those of the Arnelliaceae, Jungermanniaceae, Geocalycaceae and Scapaniaceae (Read et al 2000;). The study here, based on epifluorescence microscopy and PCR amplification of fungal ribosomal RNA genes, closely corroborates these observations, with the frequency of Serendipita being positively associated with the abundance of intracellular hyphal coils, identical to those previously recorded in European and Antarctic Diplophyllum albicans, Schistochilopsis incisa, Barbilophozia hatcheri, Trilophozia quinquedentata and Lophoziopsis excisa Newsham & Bridge 2010;Newsham et al 2014). The analyses here also indicate that Serendipita most probably does not form DS hyphae, with melanized hyphae being absent from, or present at very low levels in, specimens from which the DNA of the basidiomycete was amplified.…”
Section: Discussionsupporting
confidence: 89%
“…Whilst it is not possible to discount the possibility that the other ascomycetes recorded here are commensals with no symbiotic status, it is notable that two groups of Cladophialophora were recorded in Lophozia wenzelii, B. hatcheri and G. inflata. Cladophialophora has similarly been found to associate with species of Lophozia and Barbilophozia in North America and Antarctica (Davis & Shaw 2008;Newsham & Bridge 2010), suggesting that the genus may form symbioses with leafy liverworts, and particularly those in cold environments (Newsham et al 2014). Given the culturability of Cladophialophora (Davey & Currah 2007), we advocate that resynthesis experiments are conducted to determine the effects of the fungus on its liverwort hosts.…”
Section: Discussionmentioning
confidence: 98%
“…Less frequent are dark septate hyphae often associated with pseudosclerotia. By extrapolation from their well‐documented occurrence in seed plants (Schmid et al, ; Jumpponen & Trappe, ; Jumpponen, ; Mandyam & Jumpponen, 2005; Newsham, ; Newsham et al, ) it is reasonable to assume that these are ascomycetous. Conspicuously absent are any bona fide records of basidiomycetes.…”
mentioning
confidence: 99%
“…1 I). Newsham et al (2014). The gametophytes were clarified with 10% KOH (at room temperature, 24 h); rinsed three times in water; bleached with solution of 7.5% H 2 O 2 and 0.7% ammonium hydroxide (at room temperature, 3 min); acidified with 5% lactic acid (at room temperature, 1 h) and stained with 0.01% aniline blue in lactic acid (at room temperature, 24 h).…”
Section: Fonseca Et Al (2009) Segments Of Culturementioning
confidence: 99%